Impact of Meditation-Based Lifestyle Practices on Mindfulness, Wellbeing, and Plasma Telomerase Levels: A Case-Control Study - Dasanayaka, Nirodhi Namika; Sirisena, Nirmala Dushyanthi; Samaranayake, Nilakshi (Frontiers in Psychology, 2022)
Meditation involves psychophysical training which can result in a range of benefits including creating a calm mind and increasing self-awareness, relaxation, and tranquillity. Increasing evidence, mostly based on short-term focused interventions, suggests that meditation based activities may also have favourable effects on physical well-being including cellular aging. Hence, the aim of this study was to investigate if continued practice of meditation benefited quality of life, state of mindfulness and plasma telomerase level in healthy adults. Thirty long-term and skilled meditators were recruited from meditation centers in different parts of the island following a two-tier screening process of 70 eligible participants and 30 age and gender matched healthy non-meditators were recruited from the community. Mindfulness level and the quality of life were measured using the Five Facet Mindfulness Questionnaire (FFMQ) and Quality of Life Questionnaire, respectively while the levels of plasma telomerase enzyme were measured using Enzyme-Linked Immunosorbant Assay. Skilled meditators had a better mindfulness level (p<0.001) and quality of life (QOL) (p<0.001) than those in the comparison group. Similarly, higher plasma telomerase levels were observed in skilled meditators compared to non-meditators (p=0.002). Trait mindfulness level and plasma telomerase level showed a significant relationship with the duration of meditation practice (p=0.046 and p=0.011 respectively). Regression analysis indicated that trait mindfulness level (p<0.001) significantly predicts the plasma telomerase level. The findings of this comparative study add to the evidence on sustained benefits of meditation on well-being and healthy aging and supports incorporating meditation-based activities into lifestyle practices.